Mechanical and Thermal Characterization of Graphene and TiO2-Reinforced 4032 Aluminum Alloy for Piston Applications Using Mean Field Homogenization - Sigdel, Sachin; Dalal, Prajjwal; Sanchaniya, Sagar; Rachchh, Nikunj; Trivedi, Dhaiwat (Periodica polytechnica. Mechanical engineering - Mas̆inostroenie, 2025)
The impact of adding graphene and titanium dioxide (TiO2) nanoparticles to a 4032 aluminum alloy for use in piston applications is examined in this paper. Mori-Tanaka micromechanical modelling and mean-field homogenization were used to examine the characteristics of the composites. Mechanically, the findings demonstrated that the graphene-reinforced composite outperformed the TiO2-reinforced composite and the base material without reinforcement in terms of tensile strength, elastic modulus. The TiO2-reinforced composite, however, had a higher Poisson's ratio, suggesting that lateral deformation was more likely when crushed axially. The graphene-reinforced composite also had less overall deformation and density than the TiO2-reinforced composite and showed a lower Poisson's ratio. Thermally, the graphene-reinforced composite exhibited higher thermal conductivity, which was particularly significant for piston cooling, and showed overall higher performance characteristics for piston applications. This study sheds light on the use of Mori-Tanaka modelling and mean-field homogenization to forecast the mechanical and thermal characteristics of metal matrix composites.